Effects of Curculigo orchioides total glucosides in mouse perimenopause model of related organization and organs morphology - Cao Shan; Tian Shuo; Bai Ming; Liu Shaoyan; Jia Jiaojiao; Miao Mingsan (Bangladesh Journal of Pharmacology, 2016)
The purpose of this study was to examine the effects of Curculigo orchioides total glucosides in mouse perimenopause model. The castrated mice were treated with different doses of soybean isoflavone soft capsule, Gengnianan, C. rhizome total glycoside. Hypothalamus, thymus, spleen and uterus were collected and then fixed in 10% formaldehyde, HE staining, to observe the pathological changes of morphology. The results indicate that compared with the model group, soybean isoflavone soft capsule, gengnianan capsule and big, medium, small dose of C. rhizome total glycoside group could significantly improved the pathological changes in mouse uterus, hypothalamic, thickening of the thymic cortex and significantly increased the number of lymphocytes in the cortex, increased the volume of splenic nodule (p<0.01), in which the effect of large dose of C. orchioides total glycosides group was the best. In conclusion, C. orchioides total glucosides in mice caused by perimenopausal pathological changes of uterine, hypothalamus, spleen and other organs have good improvement effect.